Perencanaan Sistem Informasi Akademik Menggunakan Zachman Framework - Rosmiati, Rosmiati (STMIK Palangkaraya, 2017)
Academic information system planning can provide a guide in the design of academic information systems aligned with the business processes of an organization. SMK Isen Mulang yet have an Academic Information System planning are aligned with business processes. It required an academic information system planning can provide clear guidelines in the use of information technology for academic affairs at SMK Isen Mulang. Analysis of the needs required in the planning of Academic Information System using Zachman Framework approach. Each cell of the matrix Zachman discussed in depth to analyze the needs of Academic Information Systems of SMK Isen Mulang Palangkaraya. For the modeling used E-R diagrams, UML diagrams, and for examples of interface design using GUI Design Studio. The result of this research study is a vocational blueprint by using Zachman Academic Information Framework. Zachman Framework Approach to describe clearly and in detail the parts of planning academic Academic Information Systems in a simple model. This plan resulted in a blueprint that can be used as a reference are structured in making academic information system program code and test development in SMK Isen Mulang Palangkaraya.